2017
DOI: 10.2169/internalmedicine.56.7371
|View full text |Cite
|
Sign up to set email alerts
|

A Cryptogenic Case of Fulminant Fibrosing Organizing Pneumonia

Abstract: Cryptogenic organizing pneumonia (COP) generally responds well to corticosteroids with a favorable outcome. Rare cases of organizing pneumonia are rapidly progressive. Yousem et al. studied pathologic predictors of idiopathic bronchiolitis obliterans organizing pneumonia/COP with an unfavorable prognosis. Beardsley and Rassl proposed the name fibrosing organizing pneumonia (FOP). A 74-year-old female non-smoker presented with a 2-week history of dry cough followed by dyspnea and a fever. The clinical course wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…This distribution was evident in our case material where in the fibrosing DAD cases the alveolar duct connective tissue was replaced by dense collagen. A similar progression to dense collagen rich fibrosis from organizing connective tissue has also been described in organizing pneumonia under a variety of names such as fibrosing or cicatricial organizing pneumonia (49)(50)(51). The fibrosing lesions were sometimes associated with small cystic spaces.…”
supporting
confidence: 57%
“…This distribution was evident in our case material where in the fibrosing DAD cases the alveolar duct connective tissue was replaced by dense collagen. A similar progression to dense collagen rich fibrosis from organizing connective tissue has also been described in organizing pneumonia under a variety of names such as fibrosing or cicatricial organizing pneumonia (49)(50)(51). The fibrosing lesions were sometimes associated with small cystic spaces.…”
supporting
confidence: 57%
“…Histological OP has two subtypes, intraluminal type OP and incorporated type OP [18,19]. In recent reports, it was described that incorporated type OP was observed in patients of RPILD with DM and ASS [36,37]. Current study revealed for the first time that patients with influenza A (H1N1) pneumonia frequently demonstrate incorporated type OP as well.…”
Section: Discussionmentioning
confidence: 65%
“…Our patient was asymptomatic until April 2015; her symptoms had an acute onset resembling typical flu. Furthermore, clinical evidence suggests that the majority of the patients experience symptoms for less than two months [10][11][12]. However, in some patients, symptoms can persist.…”
Section: Discussionmentioning
confidence: 99%